Sources of dissatisfaction with answers to the question of the meaning of life - Mawson, T (WAM Press (Krakow, Poland), 2010)
In this paper, I seek to diagnose the sources of our dissatisfaction with answers to the question of the meaning of life. I contend that some of these have to do with the question (its polyvalence and persistent vagueness) and some have to do with life and meaningulness themselves. By showing how dissatisfaction arises and the extent to which it is in-eliminable even by God, I hope to show that we should be satisfied with our dissatisfaction.